Food system transitions in Vietnam: The case of pork and vegetable networks - Nguyen-Minh, Quoc; Prins, Heleen; Oosterveer, Peter; Brouwer, Inge D.; Vignola, Raffaele (Elsevier, 2023)
Vietnamese food systems have experienced a transition process since the late 1980s Đổi mới reforms. This paper examines the historical and ongoing transitions of pork and vegetable networks, using the Multi-Level Perspective (MLP), the Multi-Pattern Approach (MPA) and insights from food systems research. Our findings show that there was a shift from collective and self-subsistent farming to commercial small-scale farming in the late 1980s, and a rapid institutionalisation of smallholders and wet markets in the early 1990s. We argue that the current slow transition of the smallholder food regime towards improved food safety and standardisation has been locked in by the strong alignments of actors, practices and cultural values that support small-scale, fragmented production and distribution. The study suggests that those practices, values, and the needs and interests of smallholder producers and food consumers should be carefully considered when implementing transition agendas toward food safety, security, and sustainability.